A secondary data analysis of Internet use in caregivers of persons with dementia - Kim, Heejung (Nurs Open, 2014)
AIM: This paper is a secondary data analysis to investigate relationships among caregiver stress appraisal, self‐rated health and health‐related Internet use. DESIGN: Cross‐sectional correlation design. METHODS: National Alliance for Caregiving telephone survey conducted in the USA was a primary data source collected in 2009 from 258 caregivers of persons with dementia, who used the Internet to perform care‐giving tasks. Based on Pearlin's Stress Process Model, structural equation modelling was conducted. RESULTS: Caregivers with poor health reported higher levels of caregiver stress appraised, which was associated with more Internet use for health‐related purposes. It is required to develop effective Internet‐based resources to meet the needs of highly stressed caregivers of persons with dementia. However, there was no relationship between self‐rated health and health‐related Internet use in dementia caregiver.